2015
DOI: 10.1177/1468796815610354
|View full text |Cite
|
Sign up to set email alerts
|

Recruiting the “culturally compatible” migrant: Irish Working Holiday migration and white settler Canadianness

Abstract: Working Holiday programs have been identified as an increasingly significant source of temporary migrant labor for several wealthy states. This case study adds to limited work on this phenomenon in the Canadian context by offering a partial chronology of Irish Working Holiday migration to Canada and a critical analysis of Canadian government discourse that positioned Irish migrants as not only “culturally compatible” but also part of white settler Canadianness thus making them desirable workers and potential f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 48 publications
0
11
0
Order By: Relevance
“…Programs about TFWs were reformed in 2014 in the midst of our initial study; however, some of the TFW participants had permits based on programs that, today, are part of the IMP, which has become the dominant mechanism for international workers to legally work in Canada. [81][82][83][84][85] In fact, in 2017, the number of IMP work permit holders was eight times higher than that of TFWP work permit holders 3 and the effectiveness of regulatory protections for some of these workers, particularly those on a closedwork permit in the IMP, may well be equally problematic. Lack of knowledge regarding employment and OHS conditions of IMP workers is of particular concern in a context where the number of IMP workers with a closed work permit is increasing, with no compliance system in place within the program to ensure that employers follow the rules.…”
Section: Resultsmentioning
confidence: 99%
“…Programs about TFWs were reformed in 2014 in the midst of our initial study; however, some of the TFW participants had permits based on programs that, today, are part of the IMP, which has become the dominant mechanism for international workers to legally work in Canada. [81][82][83][84][85] In fact, in 2017, the number of IMP work permit holders was eight times higher than that of TFWP work permit holders 3 and the effectiveness of regulatory protections for some of these workers, particularly those on a closedwork permit in the IMP, may well be equally problematic. Lack of knowledge regarding employment and OHS conditions of IMP workers is of particular concern in a context where the number of IMP workers with a closed work permit is increasing, with no compliance system in place within the program to ensure that employers follow the rules.…”
Section: Resultsmentioning
confidence: 99%
“…Although some inequality is expected to play into a large number of situations in the realm of international relations, it is particularly illustrative in visa regimes. Remarkably, unreciprocated visa regimes may have the function to mirror inequalities between wealthy and developing countries (Helleiner 2015; Neumayer 2006, 2010). Indeed, although most visa-free regimes are negotiated as reciprocal acts, this does not apply to the prosperous Organisation for Economic Co-operation and Development (OECD) countries, whose citizens face much fewer travel restrictions than their non-OECD peers (Neumayer 2006).…”
Section: The Interaction Of Georgia and The Eu Under Asymmetry: Some mentioning
confidence: 99%
“…Studying how visa regimes have evolved from 1969 to 2010, Steffen Mau and colleagues (2015) noticed that although the free mobility for citizens of the OECD countries increased, citizens of nonaffluent countries were mostly excluded from it. In addition to these economic considerations, the perception of cultural compatibility appears to be positively related to the lifting of visa requirements (Helleiner 2015, Neumayer 2010). In this regard, Claudia Finotelli and Giuseppe Sciortino (2013) observed that the visa requirement imposed on poor Asian and African countries by EU member states were more severe that those imposed on Eastern European countries with developing economies and oil-rich economies.…”
Section: The Interaction Of Georgia and The Eu Under Asymmetry: Some mentioning
confidence: 99%
“…Canada is now the fourth OECD country with the highest number of WH makers (OECD, 2019 , 27). Despite its growing importance, this program has operated largely below the radar of public debate (Helleiner, 2017 ). Most of the focus within the Canadian literature is on migrant workers admitted under the TFWP, who are mostly workers in “low-skilled” occupations, and on their precarious status and exploitative living and working conditions (Goldring & Landolt, 2013 ; Marsden, 2018 ; Nakache & Dixon-Perera, 2015 ).…”
Section: Introductionmentioning
confidence: 99%